SYSTEMATIC LITERATURE REVIEW: METODOLOGI, TEKNOLOGI KEAMANAN, DAN BIDANG IMPLEMENTASI DALAM PENGEMBANGAN SISTEM INFORMASI BERBASIS WEB - Andi Aslam Rasyidi Rahman; Priati Assiroj; Cakra Trinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Web-based information systems are rapidly expanding across sectors, yet development methodologies and security practices remain inconsistent. This study aims to map trends in methodologies, security technologies, and implementation domains through a Systematic Literature Review (SLR). The review followed five stages: defining criteria, selecting sources, screening literature, collecting, and classifying data. Analysis of selected articles from 2021–2025 shows that the most common methodologies are Research and Development (R&D), Waterfall, and Rapid Application Development (RAD), while the adoption of Agile remains limited. In terms of security, most studies emphasize authentication and authorization, some apply encryption and data protection, and very few address web application security aligned with international standards. Regarding implementation, studies are concentrated in education, public service, and e-commerce, while finance and healthcare remain underexplored. These findings highlight research gaps in methodology adoption, security practices, and domain coverage, indicating the need for future studies to integrate modern approaches, apply international standards, and focus on critical sectors.